1997
DOI: 10.1063/1.474706
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation of Cl2O at 248 and 308 nm

Abstract: Molecular beam studies of Cl2O photolysis at 248 and 308 nm have been repeated and the analysis refined. At 248 nm, three distinct dissociation pathways that led to Cl+ClO products were resolved. At 308 nm, the angular distribution was slightly more isotropic than previously reported, leaving open the possibility that Cl2O excited at 308 nm lives longer than a rotational period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 8 publications
2
21
1
Order By: Relevance
“…If a speed dependence exists, the variations of with V should be smaller than (0.2, which is less than the variation from 0.7 to 1.5 observed by Okumura and co-workers in the 248 nm dissociation. 30 Again, there is qualitative agreement of our data with the values of Tanaka et al, who observed mean anisotropy parameters of 1.2 ( 0.2 for both spin-orbit states. 14 In fact, their value might be more reliable than ours in view of the focusing conditions in our experiment.…”
Section: B 53 Ev Anisotropysupporting
confidence: 93%
“…If a speed dependence exists, the variations of with V should be smaller than (0.2, which is less than the variation from 0.7 to 1.5 observed by Okumura and co-workers in the 248 nm dissociation. 30 Again, there is qualitative agreement of our data with the values of Tanaka et al, who observed mean anisotropy parameters of 1.2 ( 0.2 for both spin-orbit states. 14 In fact, their value might be more reliable than ours in view of the focusing conditions in our experiment.…”
Section: B 53 Ev Anisotropysupporting
confidence: 93%
“…It is known that the Hartley band ͑200-300 nm͒ of O 3 originates from excitation of the strongly repulsive branch of the B state and the involved electronic states are either repulsive or excited above their thresholds. The near ultraviolet photodissociation of Cl 2 O has been investigated in molecular beams [24][25][26][27] and in a gas cell; 28 the results indicate unity dissociation yield under low pressure conditions. 18,19 A similar argument can be applied to ClOOCl because ab initio calculations [20][21][22] and molecular beam experiments 23 suggest fast dissociation.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these authors detected a transient absorption spectrum, which they assigned to a long-lived metastable triplet state of Cl 2 O. However Moore et al [550] estimated the lifetime of this metastable excited state to be much shorter. Chichinin [167] and Tanaka et al [773], also found evidence of ground state ( 2 P 3/2 ) and spin-orbit excited ( 2 P 1/2 ) atomic chlorine products.…”
Section: -95mentioning
confidence: 99%
“…NH + NO. The recommendation is derived from the room temperature results of Hansen et al [550], Cox et al [313] and Harrison et al [553]. The temperature dependence is from Harrison et al (Table: 92-20, Note: 92-20) Back to Table C30.…”
Section: -41mentioning
confidence: 99%